2022
DOI: 10.33200/ijcer.643329
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Teacher Candidates’ Awareness of Environmental Ethics

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…It is seen that ecocentric approaches to environmental ethics are at a good level (I agree), which mean they have an environmentalist approach that takes into account the environment in terms of all living and non-living entities. Similar results were obtained in some studies conducted with teacher candidates (Çolak, 2017;Güriçin, Sevinç, 2020;Karakuş & Çimen, 2020;Özdemir, 2012;Rachmatullah, Lee, Ha, 2020;Sönmez, 2019), which points out that the teacher candidates adopt an environmentalist approach and take into account the importance of all beings living in the environment.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It is seen that ecocentric approaches to environmental ethics are at a good level (I agree), which mean they have an environmentalist approach that takes into account the environment in terms of all living and non-living entities. Similar results were obtained in some studies conducted with teacher candidates (Çolak, 2017;Güriçin, Sevinç, 2020;Karakuş & Çimen, 2020;Özdemir, 2012;Rachmatullah, Lee, Ha, 2020;Sönmez, 2019), which points out that the teacher candidates adopt an environmentalist approach and take into account the importance of all beings living in the environment.…”
Section: Discussionsupporting
confidence: 83%
“…The fact that these subjects are constantly being addressed as part of the education provided to the teacher candidates is considered to be effective. Similarly, in the studies conducted by Güriçin and Sevinç (2020), Tan (2014) and Sönmez (2019), it was observed that science teacher candidates had higher level of ethical approaches to the environment, while another study conducted with prospective science and primary school teachers (Sönmez, 2019) determined that the department was not effective. In another study conducted with students studying in economics, sociology, psychology and biology departments, no difference was found in terms of department (Özdemir, 2012).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations